A rotina de estudos de dois alunos com deficiência intelectual no contexto do ensino remoto emergencial - Costa, Samara Cristina Ferreira da (Universidade Federal de São Carlos, 2023)
In times of social distancing in the COVID-19 pandemic, it is important to reflect on the living conditions of students with intellectual disabilities (ID) and the possible impacts on their schooling. The work has the general objective of identifying and analyzing the study routine of students with ID, enrolled in elementary school II, during the period of 2020, context of remote teaching. The specific objectives are: (a) Mapping the socioeconomic and schooling profile of the family of students with ID enrolled in elementary school II; (b) describe the organization of the study routine, from the perspective of students with ID and their guardians, during remote teaching, in the period of 2020; (c) Investigate the teaching materials, supports and aids used during remote teaching for students with ID from the perspective of the family and the teacher. Data collection took place in person, following ethical procedures in necessary research. Data were collected through interviews with two students with ID, their two guardians and two teachers, totaling six interviews. From the results of this dissertation, we verified: minimization of school contents; lack of curricular adaptations; professors working without the necessary conditions and without any type of training to carry out the work effectively; impaired teaching strategies. In this, we understand that the families of people with disabilities and the people with disabilities themselves find themselves on the sidelines, without support for the necessary learning developments. Soon, the pandemic widened existing inequalities in the country, especially for students with disabilities.
The study routine of two students with intellectual disabilities in the context of emergency remote education
Keywords: Educação especial; Deficiência Intelectual; Ensino remoto; Ensino fundamental II; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO